Yamaguchi esterification: a key step toward the synthesis of natural products and their analogs—a review - Munir, Ramsha; Zahoor, Ameer Fawad; Anjum, Muhammad Naveed; Mansha, Asim; Irfan, Ali; Chaudhry, Aijaz Rasool; Irfan, Ahmad; Kotwica-Mojzych, Katarzyna; Glowacka, Mariola; Mojzych, Mariusz (Frontiers in Chemistry, 2024)
The Yamaguchi reagent, based on 2,4,6-trichlorobenzoyl chloride (TCBC) and 4-dimethylaminopyridine (DMAP), is an efficient tool for the intermolecular (esterification) reaction between an acid and an alcohol in the presence of suitable base (Et3N or iPr2NEt) and solvent (THF, DCM or toluene). The Yamaguchi protocol is renowned for its ability to efficiently produce a diverse array of functionalized esters, promoting high yields, regioselectivity and easy handling under mild conditions with short reaction times. Herein, the recent utilization of Yamaguchi reagent has been reviewed in the synthesis of various natural products such as macrolides, terpenoids, polyketides, peptides and metabolites etc.